Strategi pengembangan wisata alam Danau Tajwid di Kecamatan Langgam Kabupaten Pelalawan - Zulfikar Zulfikar; Sukendi Sukendi; Nofrizal Nofrizal (Jurnal Zona, 2021)
This research aims to determine the impact of the development of Lake Tajwid natural tourism and the strategy of developing Lake Tajwid natural tourism. There are two data in this research, namely primary data and secondary data. data analysis using GAP analysis which is based on the SAPTA PESONA indicator. Sapta Pesona has 7 indicators, namely; safe, orderly, clean, beautiful, cool, friendly and memorable. based on the results of research on natural ecotourism development of Lake Tajwid impact on environmental, economic and social conditions. the environment will have an impact on environmental pollution if it is not wise in developing tourist areas. the economic aspect can grow the economy, the social aspect opens up employment opportunities. Then there is a gap between reality and charm. The strategies designed in this research to realize the natural tourism development of Lake Tajwid are; 1) instilling awareness of tourism, 2) structuring facilities and infrastructure, 3) increasing supporting facilities, 4) increasing information / innovation and promotion, and 5) preserving the environment.